Developing and validating a new nomogram for diagnosing bladder outlet obstruction in women. Issue 1 (30th June 2017) - Solomon, Eskinder; Yasmin, Habiba; Duffy, Megan; Rashid, Tanwir; Akinluyi, Emmanuel; Greenwell, Tamsin J.
Abstract : Objective: To develop and validate a nomogram for assessing bladder outlet obstruction (BOO) in women derived from concurrent Pdet.Qmax and Q max based on radiographic evidence of increased urethral resistance. Patients and Methods: Retrospective analysis of prospectively acquired video‐urodynamics and clinical data of 185 women (development cohort) was performed. The Pdet.Qmax were plotted against Q max and cluster analysis was performed to determine an axis that best divided the definitively obstructed and unobstructed. Using data from a further 350 women (validation cohort), the sensitivity and specificity of the derived criterion was calculated. Finally, the data from both groups was pooled together and using binary logistic regression analysis, a nomogram was produced. Results: Of the 535 patients in the two cohorts, (122 [22.8%]) demonstrated radiographic evidence of BOO. Cluster analysis identified the axis that best separates the radiographically obstructed and unobstructed as Pdet.Qmax  = 2* Q max . Using the data from the validation cohort, the sensitivity and specificity for this was calculated as 0.94 and 0.93, respectively. A nomogram, representing the probability of BOO for concurrent Pdet.Qmax and Q max measurements was derived by pooling data from both cohorts. Alternatively, a female BOO index (BOOIf) may be calculated mathematically using the formula BOOIf = Pdet.Qmax  − 2.2* Q max, that is, BOOIf < 0, <10% probability of obstruction, BOOIf > 5 likely obstructed (50%) and If BOOIf > 18, obstruction almost certain (>90%). Conclusion: A female BOO nomogram (the SG nomogram) with high sensitivity and specificity is proposed. The nomogram can be used to stratify the degree of BOO or assess response to treatment.